Synergies of Food and Nutritional Sciences with Commerce and Management: A Strategic Integration for Sustainable Business (International Journal of Food and Nutritional Sciences, 2023)
This article explores the dynamic intersection between food and nutritional sciences and commerce and management, highlighting the symbiotic relationship that can drive innovation, enhance product offerings, and foster sustainable business practices. From farm to fork, the collaboration between scientific advancements in nutrition and strategic management in commerce unlocks new possibilities for businesses in the food industry. This holistic approach considers the impact on consumer trends, market dynamics, and the global supply chain, providing a comprehensive perspective for organizations seeking a competitive edge.